Environmental cues for dispersal in a filamentous fungus in simulated islands. Issue 7 (9th April 2020) - Chan, Justin Y.; Bonser, Stephen P.; Powell, Jeff R.; Cornwell, William K.
Abstract : Airborne dispersal is a key part of the life history of many saprotrophic fungi. Theory suggests a transition from growth and resource capture to airborne dispersal at some point as the resource availability in a patch declines, but in the absence of an experimental model system this theory has not been empirically tested. For saprobes, resources are arrayed in an ever‐shifting archipelago of islands with the quality of each island being defined by patch size and resource density. We tracked how Phacidium lacerum, a saprotrophic fungus, allocated resources to dispersal in small and large islands of varying resource density through production of fruiting bodies. We found that Phacidium altered the timing and rate of dispersal allocation in response to both patch size and resource density. On small resource islands, Phacidium drastically increased dispersal allocation after reaching the edge of the patch; if resource density was sufficient, on larger resource islands, Phacidium began allocation to dispersal prior to reaching the edge of the island, suggesting an additional absolute total resource level cue. These results are consistent with a two‐cue model for the switch to allocation to airborne dispersal: 1) absolute resource level controlled by the fungus, 2) the fungus' perception of patch size. This can be thought of as a mix between a full resource allocation switch (bang–bang) if the fungus perceives the patch is fully occupied with a smaller magnitude early shift (bet‐hedging) if absolute resource level crosses a threshold.